The influence of the body mass index on prognosis in women operated for breast cancer - Frączek, Jerzy; Herman, Krzysztof; Łobaziewicz, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2004)
Obesity is one of main etiological factors in many diseases including cancer. Breast cancer is the most frequent malignant neoplasm in women and it is a leading cause of death from cancer in Poland. Overweight quite often coexists with breast cancer. The aim of the study was to assess the effect of the BMI (body mass index) on prognosis in women operated for breast cancer. We analyzed 2091 women originally operated for breast cancer in 1994-2002. The mean BMI was 26.66 kg/m 2 . Patients with a higher BMI had more clinically advanced cancer. 85.3% of women received adjuvant therapy. The mean period of follow-up was 48.46 months. 97 (4.63%) women had a local recurrence of the neoplasm. With the increase of the BMI, in respective ranges, the risk of the recurrence was growing (BMI<22 kg/m 2 – 1.92%, BMI of 22-27 kg/m 2 – 4.88%, BMI>27 kg/m 2 – 5.36%). 328 patients (15.83%) died due to metastases. In the univariate analysis, BMI was a factor which insignificantly worsened prognosis in a group of ductal breast cancer patients without lymph node metastases. In the multivariate analysis only the histological degree of the tumor significantly influenced overall survival in the same group of patients. In the multivariate analysis of a group of ductal breast cancer patients without lymph node metastases, disease-free survival was significantly affected by the histological degree according to Bloom, tumor size and BMI (for patients with a normal BMI 5- and 10-year disease-free survivals were 92.7% and 87.7%, respectively, and for patients with a high BMI, the survivals were 85.1% and 78.3%, respectively, and p=0.04455). Apart from other prognostic factors obesity increased the risk of recurrence and influenced disease-free survival in breast cancer patients without lymph node metastases.